ANALISIS PENGARUH PENYULUHAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP PENGETAHUAN DAN KOMPETENSI WUS MELAKUKAN DETEKSI DINI KANKER PAYUDARA DI DESA PEJATEN SERANG BANTEN - Ika Apriyanti (Poltekkes 'Aisyiyah Banten, 2022)
Background : The only effective way that can be done for early detection of the possibility of this disease is to perform Breast Self-Examination (BSE) which can reduce the mortality rate by 25-30%. For women who have a low level of knowledge and understanding about breast cancer and how to detect it, it is necessary to provide information about breast cancer and how to detect it, namely BSE since adolescence (Viviyawati, 2014) Objective: to measure the ability of WUS on BSE, then analyze the level of change before and after being given counseling. This research was conducted in Pejaten Village, Kramatwatu Subdistrict, Serang Banten. The approach used in this research is to use a comparative approach. The research method used is to use the analytical survey method. The results showed that the knowledge of WUS in Pejaten Village about BSE experienced a very significant increase after being given counseling, knowledge at pretest was 21% good, then 83% good at posttest/after counseling. Likewise, the results on the ability to practice BSE before being given counseling 98% have not been able to do BSE, to 95% are able to do BSE after counseling. Wilcoxon test results obtained a significance value of 0.000 (p <0.05), the calculated Z value of -8.464. This means that BSE counseling has an effect on WUS knowledge about early detection of breast cancer in Pejaten Village, Serang Banten in 2022. Likewise, the Wilcoxon test results on the respondent's ability to practice BSE is 0.000 (p <0.05), the Z count value is -8.672.